The Role of Natural Physical, Mechanical, and Biochemical Barriers as Innate Immunity: A Narrative Literature Review - Septi Purnamasari; Hidayat, Rachmat (HM Publisher, 2023)
The specialized epithelial outer layer, including the skin and mucosal surfaces, is relatively resistant to most environmental hazards and resistant to infection by disease-causing microorganisms. This literature review aimed to describe the role of natural physical, mechanical, and biochemical barriers in innate immunity. The physical barrier that protects against damage and infection consists of closely related epithelial cells, including the skin and the sheet membranes that line the digestive tract, genitourinary, and breathing. The epithelial surface also provides a biochemical barrier by synthesizing and secreting substances intended to trap or destroy microorganisms (chemicals derived from the epithelium). Mucus, sweat, saliva, tears, and earwax are examples of biochemical secretions that can trap and kill potential disease-causing microorganisms. Microorganisms in the microbiome do not usually cause disease, although some are opportunistic in that they can cause disease if the integrity of the body surface is compromised or the individual's immune or inflammatory systems are damaged. In conclusion, natural barriers include physical, mechanical, and biochemical on the surface of the body and are present from birth to prevent damage by substances in the environment and prevent infection by pathogenic microorganisms.